3D-printed air-blast microfluidic nozzles for preparing calcium alginate microparticles. Issue 77 (17th October 2017) - Ye, Biao; Xu, Hong; Bao, Binbin; Xuan, Jin; Zhang, Li
Abstract : Uniform calcium alginate microparticles were prepared through 3D-printed coaxial air-blast microfluidic nozzles. Abstract : Microfluidic technologies have emerged as a promising route for precision fabrication of uniform particles. Equipment required for a traditional microfluidic device manufacturing process is expensive and production efficiency is low. It's also difficult to separate a surfactant and continuous phase impurities from particles prepared by a liquid–liquid two-phase shear method. A novel air-blast microfluidic nozzle fabricated using low-cost and efficient 3D printing technology was proposed to prepare calcium alginate particles. Effects of control parameters and solution composition on particle diameters and homogeneity were systematically investigated. Results showed that inlet air pressure has the most significant impact. A nozzle with an outlet diameter of 300 μm can produce particles with diameters ranging from 360 μm to 2100 μm. Coefficients of variation (CV) range from 5.3% to 2.2%. For the same diameter particle prepared, a smaller nozzle outlet had a narrower particle diameter distribution and needed lower inlet air pressure. This method can be used to handle high viscosity solutions and high concentrations of solutions with insoluble solid particles. The prepared particles can be used in biological and pharmaceutical fields.